Meta-Analysis of the Effect of Dietary Care on Nausea and Vomiting in Oncology Chemotherapy Patients. (31st July 2022) - He, Jing; Xiong, Ying; Mo, Dong; Tang, Min
Abstract : Objective . To evaluate the effect of dietary care on chemotherapy-induced nausea and vomiting in oncology patients. Methods . A retrospective analysis of digestive symptoms was conducted in cancer patients admitted to our hospital, who received chemotherapy, and corresponding effective dietary care countermeasures were adopted. Results . After the nursing intervention, the incidence of digestive symptoms was significantly reduced, the quality of life was significantly improved (59.92 ± 6.57) vs. (37.95 ± 7.50), and the nursing satisfaction was significantly higher (91.67% vs. 69.44%), with statistically significant differences (P < 0.05 ). Meta-analysis showed that short-term (0 to 3 months) dietary care could alleviate nausea and vomiting symptoms in chemotherapy patients (P < 0.001 ) and improve the survival quality of oncology patients (P < 0.01 ). The effect of long-term (3–6 months) dietary care on the control of nausea and vomiting symptoms in chemotherapy patients was certain (P < 0.05 ), but the effect on the improvement of their quality of life (P > 0.05 ) was unclear. Conclusion . Dietary care can alleviate the symptoms of nausea and vomiting in tumor chemotherapy patients and improve the quality of life of short-term chemotherapy tumor patients, so it can be recommended to strengthen the dietary management for tumor patients receiving chemotherapy. Patients receiving chemotherapy should be given corresponding dietary nutritional care according to their clinical symptoms in order to alleviate their adverse reactions, enhance their own immunity, and improve the prognosis of cancer patients.